Percepção de longevidade saudável em pessoas idosas pertencentes a uma zona rural: o legado da colonização italiana - Limana, Dionimara Damian (2024)
Aging is an intrinsic process of life, characterized by physical, psychological and social changes that affect each individual in a unique way. Although, historically, "old age" has been associated with inactivity and passivity, this perception has evolved in recent decades. Part of the Brazilian elderly population lives in rural areas. However, the rural elderly population faces unique challenges. To understand the perception of elderly people and their perspectives on healthy aging, longevity and quality of life in rural areas, qualitative research was carried out in the rural communities of Val de Buia and Val Feltrina, in the Municipality of Silveira Martins-RS. Elderly people aged 60 to 89 years old, of both sexes, living in these locations were included. Data collection took place from March to April 2024 with a sample of 17 people who answered a sociodemographic questionnaire and individual semi-structured narrative interview, recorded in audio. Eight interviewees were men and nine were women. More than half declared that they worked directly in agriculture, and eleven reported having some health problem. The project was approved by the Research Ethics Committee of the Federal University of Santa Maria under CAAEE 65637922.2.0000.5346. The data were qualitatively analyzed based on Bardin's Content Analysis. Two broad categories were chosen: (1) Attributi Della Cultura e Del Buon Vivere: O Legado da Cultura Italiana no Interior do Rio Grande do Sul and (2) Lavoro e Vita Rurale come Pilastri di Longevità. (1) had as defining elements the Production and Consumption of Wine, Healthy Eating, Social Living and Spirituality. (2) presents as defining elements Housing, Safety, Health and Well-being, bad weather in rural areas and work. The Italian culture of viticulture and the production and consumption of wine seem to be positive factors for longevity, as well as coexistence with nature and food without pesticides. Strong family ties and community ties have been shown to help with emotional support and a sense of belonging, although they see a need for improvements in access to specialized healthcare.